Lutzomyia longipalpis in Clorinda, Formosa province, an area of potential visceral leishmaniasis transmission in Argentina - Salomón, Oscar Daniel (2005)
Phlebotomine captures were performed during 2004 in Clorinda, Argentina. Clorinda is located across the branches of the Paraguay river in front of Asunción city, Paraguay. Reports of canine and human visceral leishmaniasis in Asunción have been increasing since 1997, however neither leishmaniasis cases nor sand flies were ever recorded from Clorinda. Light traps were located in migration paths (bridges, port), and peridomestic environments of Clorinda and surrounding localities. Lutzomyia longipalpis was found in Clorinda and Puerto Pilcomayo, first report in a potential visceral leishmaniasis transmission area for Argentina. Active surveillance is required immediately in the localities involved and the surrounding area